The effect of pathogen dosage on the pathogenicity of Neozygites floridana (Zygomycetes:Entomophthorales) to Mononychellus tanajoa (Acari: Tetranychidae) - Oduor, G.I.; Yaninek, John S.; Moraes , G.J. de; Geest, L.P.S. van der (Elsevier, 1997)
How the pathogen inoculum size affects the pathogenicity of Neozygites floridanatoMononychellus tanajoawas studied at 28°C, 12L:12D photoperiod and 90–100% RH. All inoculum sizes tested (one, two, four, six, and eight capilliconidia per mite) were lethal. Dead mites started to appear 48 hr after exposure to the conidia. Inoculum size significantly affected time to mortality. All mites exposed to six or eight capilliconidia died of mycosis 57.1 and 62.9 hr, respectively, after infection. At smaller doses, infection rates were lower, dead mites started to appear later, and time to mortality was significantly longer (between 68.7 and 89.4 hr). Most mites died within the first 6 hr of the dark phases of the photoperiod.